Performance comparison between optical wireless and mmWave/THz RF communications systems - Sakhnini, I; O'Brien, D (IEEE, 2024)
Radio-frequency (RF) systems are employing higher carrier frequencies (into the THz bands) leading to more limited link budgets. Above a particular RF carrier frequency, optical wireless communications (OW) systems can have a more favourable link budget, due to the different frequency dependence of signal propagation. In this paper, we present a study that estimates the RF carrier frequency at which this occurs, referred to as the cross-over RF frequency. The results show that there exists a cross-over RF frequency above which the OW system outperforms the RF system in terms of BER, which under LED background light can be as low as a few hundreds of GHz. Different receivers and background lighting conditions are also considered. A silicon photomultiplier (SiPM) detector is shown to outperform an avalanche photodiode (APD) detector in this background light conditions, while the latter becomes superior in higher sunlight conditions emphasising the crucial need for an optical filter for the SiPM.